Inhibitory effects of cudratricusxanthone O on particulate matter-induced pulmonary injury. Issue 3 (3rd April 2021) - Lee, Wonhwa; Ku, Sae-Kwang; Kim, Tae In; Kim, Eun-Nam; Park, Eui Kyun; Jeong, Gil-Saeng; Bae, Jong-Sup
ABSTRACT: Particulate matter 2.5 (PM2.5 ), aerodynamic diameter ≤ 2.5 μm, is the primary air pollutant that plays the key role for lung injury resulted from the loss of vascular barrier integrity. Cudratricusxanthone O (CTXO) is a novel xanthone compound isolated from the root of Cudrania tricuspidata Bureau. Here, we investigated the beneficial effects of CTXO against PM-induced lung endothelial cell (EC) barrier disruption and pulmonary inflammation. Permeability, leukocyte migration, activation of proinflammatory proteins, generation of reactive oxygen species (ROS), and histology were examined in PM2.5 -treated ECs and mice. CTXO significantly scavenged PM2.5 -induced ROS and inhibited the ROS-induced activation of p38 mitogen-activated protein kinase (MAPK). Concurrently, CTXO activated Akt, which helped maintain endothelial integrity. Furthermore, CTXO reduced vascular protein leakage, leukocyte infiltration, and proinflammatory cytokine release in the bronchoalveolar lavage fluid in PM-induced lung tissues. These results indicated that CTXO may exhibit protective effects against PM-induced inflammatory lung injury and vascular hyperpermeability.